Echo-free renal masses on ultrasound: the stethoscope as an adjunct to their diagnosis. Issue 714 (April 1985) - Suarez, R.; Lynn, A. H.
Abstract : A patient with an intrarenal arteriovenous malformation is described. Ultrasound suggested this to be a renal cyst but auscultation revealed a loud bruit and, on the basis of this, arteriography rather than cyst puncture was carried out.